Social learning in community based natural resource management project (CBNRM) : a case study of Chipembere gardening project in Zimbabwe. - Mukwambo, Robson (Rhodes University, Faculty of Education, Department of Education, 2014)
This investigation of social learning processes in the Chipembere gardening project was conducted in Rockvale village one in Sebakwe communal area in the Midlands province of Zimbabwe. In essence, the study sought to explore how the Chipembere gardening project as a community-based natural resource management initiative (CBNRM), was reflecting and supporting social learning processes of change. It also sought to enrich and deepen an organizational understanding of social learning and to generate ideas and draw recommendations that could be used to strengthen learning in other CBNRM projects. The research was undertaken as a qualitative case study with data generated through semi-structured interviews with individuals and groups. It also included an analysis of project documents and an extended period of participant observation on site and in the gardening activities. Data were indexed and coded for generating analytical memos that were used to extract and represent the scope of social learning interations within the developing project. The study found that within the Chipembere gardening project a wide range of learning interactions were significant in shaping the developing project. Furthermore, these interactions were earmarked as the major drivers of social learning processes within the project. The study concluded that the social learning interactions amongst the gardeners in the Chipembere community garden were instrumental in fostering change that enhanced community livelinhoods and wellbeing.
Keywords: Social learning -- Zimbabwe; Social learning -- Case studies; Vegetable gardening -- Zimbabwe; Economic development projects -- Zimbabwe